Neo-Assyrian and Greek Divination in War : Ancient Warfare Series Volume 3 - Ulanowski, Krzysztof, (Culture and History of the Ancient Near East ;, 2021)
Neo-Assyrian and Greek Divination in War focuses on all divinatory practices which were used in the ancient Near East and Greece in time of war. Divination was a practical way of discovering the will of the gods, and enabled human contact with the divine. Divinatory practices were crucial to decision-taking. The results of divination were especially important during war. This book concentrates on the methods used to obtain all possible information from the divine world which could impact on the results of war. Knowledge of divine plans, verdicts and favors would ensure victory, power and eternal glory. This book is also about the convergence of the ancient Near East and Greek divinatory systems, methods and practices. Step by step, it points out that the Greeks treated divination in a very similar way to the Mesopotamians, and presents the possible routes of transmission of this divine knowledge, which was practiced in both cultures by a group of well-trained professionals.